Development of a Sensor-Based Glove-Controlled Mobile Robot for Firefighting and Rescue Operations - Sneineh, Anees Abu; Salah, Wael A. (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
Robots are important in preventing hazards. This paper presents the construction and testing of a mobile robot equipped with a sensor-based glove for firefighting and rescue operations. The main idea is based on the ability to control the mobile robot through the movement of a gloved hand. The glove circuit is connected to the robot circuit through Bluetooth. The MPU6050 gyroscope sensor detects the movement of a gloved hand and sends the direction of the hand’s inclination to the microcontroller, which in turn uses this information to direct the mobile robot’ movement in the desired direction. Experiments were conducted to test the mobile robot and its control system. Results showed that the robot prototype works effectively with satisfactory response to the intended direction of robot movement. An increase in safety level and a reduction in firefighting risks were also observed. The proposed robot can assist effectively in rescue operations, creating opportunities for future improvements.